Pendidikan Kepemimpinan Kristen Sebagai Fondasi untuk Mencetak Generasi Muda Yang Berintegritas di Masa Depan (International Forum of Researchers and Lecturers, 2025)
Leadership plays a crucial role in shaping a better future, particularly within the context of education. This article examines the significance of leadership education as a foundation for developing future leaders who are characterized by integrity, vision, and competence. Through both theoretical and practical approaches, this study explores the fundamental leadership principles relevant to the educational sphere and effective strategies for their implementation. Leadership education is not merely a process of knowledge transfer but also an effort to build character and strengthen moral values. Therefore, leadership education plays a pivotal role in producing a new generation of leaders capable of facing global challenges wisely and responsibly. This article is expected to provide fresh insights for educators, educational leaders, and policymakers in formulating holistic and sustainable educational programs.